BIOMASSA DI ATAS TANAH DAN PENGHITUNGAN SIMPANAN KARBON HUTAN KALIBIRU KABUPATEN KULON PROGO - Arsalan, Andy; Gravitiani, Evi; Irianto, Heru (Universitas Muhammadiyah Surakarta, 2020)
Above Ground Biomass (AGB) forest ecosystem is one of the fundamental parameters to describe each of its functions. Carbon in the forest ecosystem accumulates through absorption of CO2 in the atmosphere and is assimilated into biomass. The study of forest vegetation biomass is important for determining carbon storage in dominant tree components and calculating carbon cycles at regional and global levels. Kalibiru Forest carbon storage information is not yet available, so it is necessary to calculate carbon potential. This study aims to calculate aboveground biomass and estimate carbon stocks in the Kalibiru Forest. The study was conducted in Kalibiru Hamlet, Hargowilis Village, Kokap District, Kulon Progo Regency. The research conducted the indirect method (non-destructed) to calculate biomass and carbon by using the allometric equation. Base on the calculation, Kalibiru Forest has 5.086,52 tons of biomass or 175,40 tons per hectare in average. The potential for carbon storage in the Kalibiru Forest is 2.543,26 tons of carbon or 87,7 tons per hectare in average. This figure means that preserving 1 hectare of Kalibiru Forest can avoid the impact of atmospheric damage due to the greenhouse gas effect as many as 87,70 tons per year. Results of this study provide an insight for the surrounding community about the importance of the existence of the Kalibiru Forest as an absorber of CO2 gas in the atmosphere. As another benefit, it provides motivation for the surrounding community to continue in preserving the forest.